Penerapan Metode Jigsaw dalam Materi PAI Meneladani Kemuliaan Rasul Allah SWT di SMPN 1 Karawang Timur - Dede Rahmatulloh; Ajat Rukajat; Khalid Ramdhani (FONDATIA, 2022)
The background of this research is to analyze the value of the effect of the Jigsaw Method in class VII learning. The aims of this study were to (1) determine the learning process of Islamic Religious Education and Morals before using the Jigsaw method; (2) Knowing the learning process of Islamic Religious Education and Character after using the Jigsaw method; and (3) Knowing the inhibiting and supporting factors of the learning process of Islamic Religious Education and Morals. The method used in this research is descriptive qualitative. The research subject is the influence of the Jigsaw method in the learning process of Islamic religious education and character. Data analysis results with descriptive qualitative techniques, the results of the research researchers obtained the influence of the Jigsaw method contained in the learning process. The results of the study indicate that there is a relationship between the Jigsaw method, namely: a) Reading: students accept topics and read the material provided to find information; b) Expert or expert group discussion: students who discuss the same topic meet to discuss it in expert groups; c) Group report: experts return to their respective groups and explain their topic to their group members; d) Tests: students take individual tests that contain all topics; e) Group rewards: group scores are calculated. The results of the value analysis of the influence of the Jigsaw Method on Improving the Learning Process of Islamic Religious Education & Morals for Grade VII in the Material of imitating the glory of Allah's Apostle at SMPN 1 Karawang Timur.